Protonmotive force and motility of Bacillus subtilis. - Shioi, J I (1978)
Motility of Bacillus subtilis was inhibited within a few minutes by a combination of valinomycin and a high concentration of potassium ions in the medium at neutral pH. Motility was restored by lowering the concentration of valinomycin or potassium ions. The valinomycin concentration necessary for motility inhibition was determined at various concentrations of potassium ions and various pH's. At pH 7.5, valinomycin of any concentration did not inhibit the motility, when the potassium ion concentration was lower than 9 mM. In the presence of 230 mM potassium ion, the motility inhibition by valinomycin was not detected at pH lower than 6.1. These results are easily explained by the idea that the motility of B. subtilis is supported by the electrochemical potential difference of the proton across the membrane, or the protonmotive force. The electrochemical potential difference necessary for motility was estimated to be about -90 mV.